Activin B promotes the initiation and progression of liver fibrosis. Issue 10 (22nd July 2022) - Wang, Yan; Hamang, Matthew; Culver, Alexander; Jiang, Huaizhou; Yanum, Jennifer; Garcia, Veronica; Lee, Joonyong; White, Emily; Kusumanchi, Praveen; Chalasani, Naga; Liangpunsakul, Suthat; Yaden, Benjamin C.; et al.
Abstract: The role of activin B, a transforming growth factor β (TGFβ) superfamily cytokine, in liver health and disease is largely unknown. We aimed to investigate whether activin B modulates liver fibrogenesis. Liver and serum activin B, along with its analog activin A, were analyzed in patients with liver fibrosis from different etiologies and in mouse acute and chronic liver injury models. Activin B, activin A, or both was immunologically neutralized in mice with progressive or established carbon tetrachloride (CCl4 )–induced liver fibrosis. Hepatic and circulating activin B was increased in human patients with liver fibrosis caused by several liver diseases. In mice, hepatic and circulating activin B exhibited persistent elevation following the onset of several types of liver injury, whereas activin A displayed transient increases. The results revealed a close correlation of activin B with liver injury regardless of etiology and species. Injured hepatocytes produced excessive activin B. Neutralizing activin B largely prevented, as well as improved, CCl4 ‐induced liver fibrosis, which was augmented by co‐neutralizing activin A. Mechanistically, activin B mediated the activation of c‐Jun‐N‐terminal kinase (JNK), the induction of inducible nitric oxide synthase (iNOS) expression, and the maintenance of poly (ADP‐ribose) polymerase 1 (PARP1) expression in injured livers. Moreover, activin B directly induced a profibrotic expression profile in hepatic stellate cells (HSCs) and stimulated these cells to form a septa structure. Conclusions : We demonstrate that activin B, cooperating with activin A, mediates the activation or expression of JNK, iNOS, and PARP1 and the activation of HSCs, driving the initiation and progression of liver fibrosis. Abstract : We found that activin B promotes hepatocyte injury and activates hepatic stellate cells, mediating the initiation and progression of liver fibrosis. Thus, we for the first time demonstrate activin B as a novel and strong profibrotic factor.image